emberian Edukasi dan Pelatihan Pembuatan Sabun Cuci Piring dari Limbah Kulit Buah Nanas - Ningrum, Wulan Agustin; Waznah, Urmatul; Rahmasari, husna Santika (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The results of pineapple processing are known to produce pineapple skin waste which is valuable as waste or animal feed. This is due to the lack of knowledge that farmers have regarding organic waste processing. This community service activity aims to increase public knowledge about the use of pineapple peel waste as hand washing soap. The method of implementing this activity is to provide educational counseling through lectures on the use of pineapple peel waste and provide training on how to make dish soap from pineapple peel waste to community service participants. This service activity is expected to be able to have a positive impact and good learning for the community in developing knowledge related to the use of pineapple peel which has been only thrown away. The results of this activity indicate an increase in knowledge which is known from the post test results of 83% and from the results of the community questionnaire states that this activity was very interesting.